Urolithin A’s Antioxidative, Anti-Inflammatory, and Antiapoptotic Activities Mitigate Doxorubicin-Induced Liver Injury in Wistar Rats - Shahid Karim; Batoul Madani; Abdulhadi S. Burzangi; Mohammed Alsieni; Mohammed A. Bazuhair; Maha Jamal; Hussam Daghistani; Mohammed O. Barasheed; Huda Alkreathy; Mohammad Ahmed Khan; Lateef M. Khan (Biomedicines, 2023)
Human colon microbiota produce a metabolite called urolithin A (URO A) from ellagic acid and linked compounds, and this metabolite has been demonstrated to have antioxidant, anti-inflammatory, and antiapoptotic activities. The current work examines the various mechanisms through which URO A protects against doxorubicin (DOX)-induced liver injury in Wistar rats. In this experiment, Wistar rats were administered DOX intraperitoneally (20 mg kg−1) on day 7 while given URO A intraperitoneally (2.5 or 5 mg kg−1 d−1) for 14 days. The serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and gamma glutamyl transferase (GGT) were measured. Hematoxylin and eosin (HE) staining was used to evaluate histopathological characteristics, and then antioxidant and anti-inflammatory properties were evaluated in tissue and serum, respectively. We also looked at how active caspase 3 and cytochrome c oxidase were in the liver. The findings demonstrated that supplementary URO A therapy clearly mitigated DOX-induced liver damage. The antioxidant enzymes SOD and CAT were elevated in the liver, and the levels of inflammatory cytokines, such as TNF-α, NF-kB, and IL-6, in the tissue were significantly attenuated, all of which complemented the beneficial effects of URO A in DOX-induced liver injury. In addition, URO A was able to alter the expression of caspase 3 and cytochrome c oxidase in the livers of rats that were subjected to DOX stress. These results showed that URO A reduced DOX-induced liver injury by reducing oxidative stress, inflammation, and apoptosis.